Association between Rainy Season and Diarrhea in 13- to 24-Month-Old Toddlers - Jeceline Sutarto; Edward Surjono (Majalah Kedokteran Bandung, 2020)
Diarrhea is the second leading cause of death in children under five year and is considered a prevailing problem in many developing countries, including in Indonesia. Diarrhea is a multifactorial disease and season is suggested as one of the attributing factors of this disease. This study aimed to identify the association between the rainy season and diarrhea in 13- to 24-month-old toddlers. This was a cross-sectional analytical observational study on medical records of 13- to 24-month-old-toddlers with infectious diarrhea who visited Penjaringan I Sub-district Public Health Center, North Jakarta, Indonesia from 2016 to 2019 that included three cycles of the rainy and dry seasons. Data collection was performed in March 2020 and 286 medical records were included in the study. The relationship between the independent and dependent variables was analyzed using chi-square. Of the total cases, 83 cases occurred in rainy season and 203 cases occurred in dry season (p=0.291). Diarrhea was seen in girls aged13–16 months. There is no significant association between rainy season and diarrhea.Hubungan Musim Hujan dengan Diare pada Balita Usia 13–24 Bulan Diare merupakan penyebab kematian balita nomor dua di dunia yang masih menjadi masalah pada banyak negara berkembang, termasuk Indonesia. Diare adalah sebuah penyakit multifaktorial. Musim merupakan salah satu faktor yang mempengaruhi diare melalui dampaknya pada lingkungan. Penelitian ini bertujuan mengetahui hubungan musim hujan dengan kejadian diare pada usia 13–24 bulan. Penelitian ini merupakan penelitian analitik observasional dengan metode potong lintang. Pengumpulan data dilakukan pada bulan Maret 2020 di Puskesmas Kelurahan Penjaringan I, Jakarta Utara, dengan menggunakan rekam medis periode tahun 2016–2019, yang meliputi masing-masing tiga siklus musim hujan dan musim kemarau. Sampel penelitian adalah usia 13–24 bulan yang didiagnosa dengan diare infeksi. Hubungan antara variabel independen dan dependen diuji menggunakan chi-square. Dari 286 rekam medis yang digunakan, 83 kasus terjadi sewaktu musim hujan dan 203 kasus terjadi sewaktu musim kemarau (p=0,291). Kejadian diare paling tinggi pada perempuan kelompok usia 13–16 bulan. Tidak terdapat hubungan bermakna antara musim hujan dengan kejadian diare.